Evil star - Horowitz, Anthony, 1955- (New York : Scholastic Press, 2006)
Having locked the Raven's gate, fourteen-year-old Matt travels to Peru where he meets the second of the five gatekeepers and works with him to try to stop the opening of a second gate somehow related to the Nazca Lines.
"Book two of The Gatekeepers"--Cover.
680
Accelerated Reader AR
Keywords: Incas -- Juvenile fiction; Indians of South America -- Peru -- Juvenile fiction; Nazca Lines Site (Peru) -- Juvenile fiction; Peru -- Juvenile fiction; Science fiction; Paranormal fiction